Effects of an animated teaching tool on deaf students' comprehension of whole numbers - Reyes, Liezel Aquino; Bustos, Marie Therese Angeline P.; Ocampo, Anthony C.; Ganaden, Mildred S.; Sibbaluca, Luzviminda M. (Quezon City College of Education, University of the Philippines Diliman, 2013)
The study focused on an Animated Teaching Tool as an instructional teaching tool in teaching the Comprehension of Whole Numbers. Specifically, it sought to determine the effects of Animated Teaching Tool in improving the performance of Grade 1 deaf students in the Comprehension of Whole Numbers through Comprehension of Whole Numbers Test.
Two comparable groups of Grade 1 deaf students from San Jose Elementary School and Kasiglahan Village Elementary School as the experimental group and traditional group respectively, were chosen in the study and were taught by the researcher. Both classes met for 60 minutes per meeting, Monday through Friday.
The deaf students were given a pretest and a post test using the Comprehension of Whole Numbers Test (CWNT). The CWNT assessed students’ comprehension from the adjusted budget of work of Mathematics for the First Quarter Period of SY 2012-2013. A teaching strategy that included the use of chalk and board plus limited visual aids was utilized for the traditional group while an alternative teaching strategy using Animated Teaching Tool, was applied to the deaf students in the experimental group. This teaching tool presents concepts in animation. Filipino Sign Language was used as medium of instruction in both groups.
The scores in the pretest and posttest of the participants were tabulated and used to determine the improvement of the Grade 1 deaf students’ Comprehension of Whole numbers in the animated group and traditional group. The Mann-Whitney test, the non parametric equivalent of the independent t-test, was utilized in the treatment and analysis of data gathered.
Findings reveal that exposure to Animated Teaching Tool results to a significantly better Comprehension of Whole Numbers than exposure to the traditional teaching approach. The researcher observed that deaf students showed more confidence in answering and showed competitiveness among their classmates. Also they gravitated towards the interactiveness of the tool.
With this, the researcher encourages the use of Animated Teaching Tool as an alternative teaching tool to improve the Grade 1 deaf students’ Comprehension of Whole Numbers.
Thesis
Keywords: Animation (Cinematography).; Numbers, Natural; Mathematicsy -- Study and teaching (Elementary) -- Philippines -- Rodriguez (Rizal).; Deaf children -- Education -- Philippines -- Rodriguez (Rizal).; First grade (Education) -- Philippines -- Rodriguez (Rizal).